Seeking connections across constellations: a reflection on Tom O'Regan. Issue 3 (4th May 2021) - Bode, Lisa
ABSTRACT: This article reflects with affection on the work of the late Professor Tom O'Regan, in his interwoven capacities as scholar, teacher, colleague, friend, catalyst, and generous mentor to younger scholars. It attempts to convey the intellectual openness, curiosity, and conversations with others that shaped his research in Media and Cultural Studies, and to make visible the skeins of connective tissue across his many collaborations and projects. It traces the recent trajectories of his ideas from cultural discourse to policy, to audience measurement, to media platforms and algorithmic culture. It attends to his particular ability to see how seemingly disparate people, events, objects, and ideas related to each other, and to bring these elements into conversation with each other. Tom O'Regan's desire to map interlocking systems of media, of technology, of institutions, of culture, was always geared towards an understanding of where points of intervention could best happen. I argue that his long-standing attachment to the writings of Michel Foucault and Bruno Latour did not just shape his research, but also his sense of his own role, responsibilities, and capacity to act in the service of others within the structures and networks of the contemporary Australian university.